Molecular design of potential anti-tumor drug candidates via NF-κB pathway gene inhibition - Nonato, Maybel (Animo Repository, 2013)
Advancements in technology have provided many answers for creating new compounds and improving existing ones. It has also allowed researchers to create drug lead molecules according to their preferences. Through this, trial and error method in drug design has been reduced. Furthermore, drug design is now less time consuming and cost-efficient with the use of computer aided drug design (CADD). In this study, CADD is used to create IKK and p50 inhibitor candidates deemed to possess better specifically and potency in targeting the NF-kB gene. The candidate inhibitors were designed utilizing ligand based drug design techniques in compliance with established confidence levels of their relevant chemical descriptors. The theoretical candidate inhibitors that were designed showed a high degree of possibility to be an anti-inflammatory drug and consequently, as anti-tumor agents.